The Teachers’ Manners in Language Use and Classroom Management Interaction in Senior High School - Thoyib, Mastur (STKIP PGRI SITUBONDO, 2024)
The purpose of this paper is to investigate the teachers’ manners in language use and classroom management interaction in senior high school. A descriptive research design was adopted in this study. The purpose of this study is to address the research questions,